PERAN PENYULUH BKKBN DALAM MENCEGAH PERNIKAHAN USIA DINI - Andi Syahraeni (Jurusan Bimbingan dan Penyuluhan Islam, 2022)
BKKBN is a non-ministerial government agency that is under the President and is responsible to the President based on Law Number 52 of 2009 article 56 paragraph (2), the BKKBN is tasked with carrying out population control and carrying out family planning. In 2020 the BKKBN has carried out organizational restructuring with the promulgation of the National Population and Family Planning Agency Regulation Number 11 of 2020 concerning the Organization and Work Procedures of the BKKBN. Early marriage in Indonesia has become a phenomenon that often occurs in almost all regions. Early marriage is a social problem that occurs among adolescents. The most victims of early marriage are women. Disobedience to the minimum age limit for marriage as stipulated in the marriage law, is evident from the 2017 BPS report which shows that the number of early marriages is ranked high with a relevance level of 25.71% and occurs evenly in almost all provinces in Indonesia. Even more astonishing, not only are they tall, but if you look at the data by segregation (gender), the number of girls is higher, that is, one out of four girls in Indonesia are victims of early marriage. The Messenger of Allah emphasized that